Hubungan Antara Dukungan Keluarga Dan Motivasi Kontrol Gula Darah Pasien Diabetes Mellitus Tipe 2 Di Klinik Kartika Husada Sitimulyo Piyungan Bantul - Saputra, Danang; Sutanta, Sutanta (STIKES Wira Husada Yogyakarta, 2015)
ABSTRACT Diabetes mellitus is a degenerative disease that is expected to continue to increase its prevalence. Family support can strengthen individuals, motivate individuals to maintain or improve the health and health motivation. Motivation is the strength, encouragement, needs, pressure or mechanism spirit, psychology, which encourages a person to achieve a particular goal or accomplishment in accordance with what he wants. This study was to know the relationship between family support and blood sugar control zmotivation Diabetes mellitus type 2 patients at the Clinic Kartika Husada Sitimulyo Piyungan Bantul. This research analytic cross sectional survey. Total population of 50 patients with Diabetes mellitus type 2 with a sample of 30 patients were taken using purposive sampling. Collecting data using the enclosed questionnaire. Data analysis using Spearman rank correlation. Support families of patients with type 2 Diabetes mellitus for the control of sugar virgin in both categories as much as 60% and quite as much as 40%. Motivation relatives of patients with type 2 Diabetes mellitus who have the motivation to control blood sugar in both categories as much as 86.7%, quite as much as 10% and less by 3.3%. There is a significant relationship between family support and motivation blood sugar control patients Diabetes mellitus type 2. There is a relationship between family support and motivation of the patients blood sugar control in type 2 Diabetes mellitus.